Using Remote Sensing Systems to Study Land Degradation and Environmental Risks in Baghdad City for the Period 1990-2023 - Yasser Y. Khudair; Mohammed F. Majeed; Ahmed F. Hasan; Ahmed A. Khaleefa (Genius Journals, 2024)
Baghdad city faces numerous environmental problems due to various factors, with urban expansion being the most prominent. Urban growth, neglect of existing infrastructure development, and the absence of new infrastructure construction have exacerbated these problems and environmental risks. The research aimed to study and analyze complex environmental processes in Baghdad, such as land deformation, degradation, and associated risks, using remote sensing systems. The key findings indicate that Baghdad city faces various environmental risks threatening its inhabitants and the urban environment. These risks include increasing desertification and drought rates, the spread of dust storms, and sewage discharge into nearby areas, posing significant health risks such as soil and air pollution. Waste disposal, managed by the capital's municipality, presents a significant problem in transportation and the disposal process, whether through burial or burning, contributing to significant pollution due to inadequate planning. Recommendations include implementing strict laws and measures to preserve Baghdad's environment and removing activities causing pollution and distortion of its beautiful image.
Keywords: Remote Sensing; Land Degradation; Environmental Risks